PHYSICAL EDUCATION LEARNING MEDIA BASED ON TRADITIONAL SURAKARTA CHESS FOR CHARACTER EDUCATION AND NUMERACY IN ELEMENTARY SCHOOLS - Fadlu Rachman; Andri Prasetiyo; Zikrur Rahmat; Tatang Iskandar; Sri Novita Sari (Program Studi Pendidikan Jasmani, FKIP Universitas Bina Bangsa Getsempena, 2026)
This study aims to develop a physical education instructional medium in the form of a board game based on the traditional game Catur Surakarta to strengthen character education and numeracy literacy among elementary school students. The research subjects were fifth and sixth grade students at MIN 1 Pesawaran. In addition, this study also seeks to evaluate the quality of the developed board game in terms of its validity and practicality. The research method refers to the ADDIE development model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The results of the study indicate that: (1) the board game instructional medium demonstrates a high level of validity, as evidenced by an average score of 0.91 for content feasibility (high category), 0.85 for media feasibility (high category), and 0.70 for game feasibility (valid category); and (2) the practicality based on teacher and student response questionnaires is classified as very practical, with an average score of 96%. Overall, the board game instructional medium based on the traditional game Catur Surakarta is declared valid and practical for use in Physical Education learning at the elementary school level.